Revealing the Re-transformation of 9 Summers 10 Autumns - Adji, Alberta Natasia (UI Scholars Hub, 2018)
9 Summers 10 Autumns (2011) is an autobiographical novel about a young man from a small city of Batu who later succeeds in pursuing his dream by working in the United States. The novel was written based on Iwan Setyawan’s life story and it was made into a movie by the same title in 2013. Two years later, the movie was adapted into an augmented motion picture hinted illustrative book which combines novel, comic, app, and movie together. This phenomenon of re-transformation of a literary work is said to be the first of its kind in Indonesia and has somewhat contributed to the rising trend of movies adapted into books or comics in Indonesia, such as Assalamualaikum Beijing (2015) and Ada Apa dengan Cinta? (What’s Up with Love?) (2016). This study examines Iwan Setyawan’s strategy for achieving legitimacy in the arena of Indonesian literature through his motivational rags-to-riches ideals which are depicted in the book. The discussion is carried out by applying Pierre Bourdieu’s field of cultural production theory, as well as the sociology of literature approach, in order to highlight the phenomenon of transformation from novel into movie and eventually into an augmented motion picture hinted illustrative book. Later, this study discovered that the phenomenon has changed the image of Indonesian art and literary world. It proves that such prestigious legitimacy can now be achieved through commercial strategies, making it seem dynamic, but at the same time questionable in its most authentic sense.